GAMBARAN KADAR GLUKOSA DARAH SEWAKTU PADA WANITA MENOPAUSE DI KELURAHAN BITERA KECAMATAN GIANYAR - Kadek Aprilya; I Nyoman Gede Suyasa; Ni Nyoman Astika Dewi (Poltekkes Kemenkes Denpasar, 2022)
energy which is absorbed in large quantities into the blood and converted in the liver. Increased body fat in menopausal women has an important role in the development of insulin resistance after menopause which can increase blood glucose levels. Purpose The purpose of this study was to determine the description of blood glucose levels in menopausal women in Bitera Village, Gianyar District. Method used in is a descriptive research conducted in January – May 2022 with a total of 60 respondents obtained by random sampling technique. Blood glucose levels were measured by the Point Of Care Testing (POCT) method. Result showed that menopausal women with blood glucose levels (1.67%) in the low category, (56.67%) in the normal category, and (41.67%) in the high category. Age group Blood Glucose levels When high the age group 50-54 years as much as (36.00%). Blood Glucose Levels When high were more commonly found in the fat BMI category (72.00%). Based on physical activity, menopausal women who sometimes have blood glucose levels while doing sports (80.00%). Menopausal women who do not have a hereditary history of diabetes are more dominant in having blood glucose levels over time as much as (52.00%). Conclusion The categories of respondents who have high blood glucose levels of age group 50-54 years, fat BMI, moderate physical activity, and no hereditary history of diabetes.